Foreign ownership as a moderating factor in transfer pricing: Evidence from multinational firms in Indonesia - Yuliana, Indah; Rasheeda, Salma; Putri, Oggy Maulidya Perdana (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2026)
This study examines the relationship between taxation, tunneling incentives, foreign ownership, and transfer pricing among multinational companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Using purposive sampling, 27 firms were selected, resulting in 81 firm-year observations. The study employs multiple linear regression and moderated regression analysis (MRA) to assess both direct and interaction effects. The results show that taxation is not statistically significantly associated with transfer pricing, whereas tunneling incentives are negatively and significantly associated with it. Furthermore, foreign ownership plays a significant moderating role, strengthening the relationships between taxation and transfer pricing and between tunneling incentives and transfer pricing. These findings indicate that transfer pricing decisions are shaped by the interaction between internal governance mechanisms and external ownership structures rather than by individual factors in isolation. This study contributes to the literature on transfer pricing behavior in developing economies by highlighting the conditional role of foreign ownership. However, the model does not incorporate several potential control variables, such as firm size, profitability, leverage, and industry characteristics. Future research is therefore encouraged to include additional firm-level and macroeconomic variables to improve the model’s robustness and explanatory power.